Scientific- Theoretical Importance of Jurisdiction in Conducting Civil Court Cases - Muxtorov Sadkamol Valiyevich (Scholar Express Journals, 2023)
Scientific- Theoretical Importance of Jurisdiction in Conducting Civil Court Cases